An Epistemological Study on Somantri’s Thought about the Social Studies as a Synthetic Discipline - Mohammad Imam Farisi; Udin S. Winataputra; I.G.A.K. Wardhani (Journal of Education and Learning (EduLearn), 2015)
This study examines Somantri’s thought about the epistemology of social studies as a scientific discipline. The Study is a qualitative-interpretive (philosophical inquiry) using his academic works as a primary source, and related expertise references as secondary sources selected by annotated bibliography and literature review techniques; then analyzed by a qualitative content analysis technique. The results of the study show, epistemologically, the social studies within Somantri’s thought conceptualized as a synthetic discipline and an integrated educational program, a product of synergistic reengineering from two or more disciplines equivalent for the social studies purposes. The synthetic discipline is the nature, identity, and a culture of faculty and postgraduate of the social studies. It has four academic status namely ‘advance knowledge’, ‘middle-studies’, ‘primary structure’; and ‘integrated educational program’ developed at all levels of the school and teachers’ college.